Embarking on the Path of Serenity: Unraveling the Impact of Buddhist Meditation on Modern Life in Bandung - Jajang Nasserie Djamaludin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2023)
The inexorable flow of modernity throughout the world has changed the fabric of life tremendously, leading to various social problems. In response to this, religious individuals, who already have standardized guidelines in their lives, are seeking ways to navigate and address the complexities brought on by modernization. This research delves into the impact of meditation practiced by Buddhists in Bandung, West Java, utilizing a qualitative method. The study unravels the profound influence of meditation on the pattern of daily life, emotional regulation, and overall mental well-being of the meditators. The findings indicate that regular meditation practice not only cultivates a calmer and composed mindset but also enhances the ability to cope with stress, facilitates emotional control, and fosters quicker problem-solving skills in their everyday activities. Moreover, the research sheds light on how meditation serves as a transformative tool, leading to increased wisdom and tranquility, ultimately aiding individuals in seeking enlightenment and attaining ultimate happiness amidst the challenges of modern life. The significance of this research in academia lies in its contribution to a deeper understanding of the transformative impact of Buddhist meditation on daily life and mental well-being, providing valuable insights into the role of meditation practices in navigating the complexities of modernity.